Vegetation composition, diversity, stand structure, and carbon storage of Lolkisale Village Land Forest Reserve in the Northeastern part of Tanzania - EZEKIEL EDWARD MWAKALUKWA; ANDREW MWAKISU; SAMI MADUNDO; SALIM MOHAMMED SALIM MALIONDO (Smujo International, 2023)
Abstract. Mwakalukwa EE, Mwakisu A, Madundo S, Maliondo SMS. 2023. Vegetation composition, diversity, stand structure, and carbon storage of Lolkisale Village Land Forest Reserve in the Northeastern part of Tanzania. Nusantara Bioscience 15: 79-90. Little is known about the effects of human activities on the condition of the Lolkisale Village land Forest reserve located in Monduli District, Arusha region, in the northeastern part of Tanzania. This study assessed the status of woody species diversity, composition, structure, and available potential of the forest on carbon storage. The vegetation data were collected from 33 concentric sample plots of 5 m, 15 m, and 20 m radius laid systematically across the forest area of 960 ha. A total of 58 plant species belonging to 30 families were identified. Diversity indices have indicated a high woody species diversity in the forest reserve. The most important species were Commiphora schimperi (O.Berg) Engl., Dombeya rotundifolia (Hochst.) Planch., Acacia tortilis (Forssk.) Hayne, and Combretum molle R.Br. ex G. Don. Stand structure comprises 190 ± 117 stems ha-1, basal area of 7.68 ± 5.17m2ha-1 and standing volume of 64.04 ± 45.85 m3ha-1, while the mean above-ground carbon stocks and the mean below-ground carbon stocks were 19.55 ± 13.38 Mg C ha-1 and 3.91 ± 2.68 Mg C ha-1 respectively. Generally, the reserve was found to be in good condition. The observed high diversity of woody species signifies the importance of legally protecting this area as a village land forest reserve. In addition, quantifying other carbon pools, such as soil, dead wood, and surface litter, should be considered for estimating this forest's total carbon stock potential. In this regard, measures to control the use of the forest as a grazing area would be useful to allow new regrowth and young trees to attain maturity stages without being interfered with by the livestock.